2020
DOI: 10.1108/jibr-09-2019-0276
|View full text |Cite
|
Sign up to set email alerts
|

Employer branding through crowdsourcing: understanding the sentiments of employees

Abstract: Purpose The purpose of this paper is to explore the role of social media in creating an attractive employer brand for any organization. It investigates one of the social media Glassdoor, which is an online employer branding platform, where employees put their reviews which are both positive and negative. Analysis of these reviews can generate a lot of insights into employer branding. Design/methodology/approach The data was collected as 1,243 reviews from Glassdoor, an online crowdsourced employer branding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 69 publications
2
52
0
Order By: Relevance
“…According to marketing research, positive e-WOM generates a positive attitude and recommendation for purchase, whereas negative e-WOM has the opposite effect [33]. Empirical human resources (HR) studies also found that employee experience leads to both positive and negative e-WOM [3], and positive (negative) e-WOM leads (or not) to recommendations of employers as employers of choice [8]. Glassdoor provides different employer rating scales and invites participants to paint a whole picture of what it is like to work for an employer [34], and these scales represent different EVP promises fulfilled by an employer, including overall rating, culture and values, work-life balance, senior management, compensation and benefits, and career opportunity based on a five-point (star) scale.…”
Section: Crowdsourced Employer Ratings and Employee Recommendations Omentioning
confidence: 99%
See 3 more Smart Citations
“…According to marketing research, positive e-WOM generates a positive attitude and recommendation for purchase, whereas negative e-WOM has the opposite effect [33]. Empirical human resources (HR) studies also found that employee experience leads to both positive and negative e-WOM [3], and positive (negative) e-WOM leads (or not) to recommendations of employers as employers of choice [8]. Glassdoor provides different employer rating scales and invites participants to paint a whole picture of what it is like to work for an employer [34], and these scales represent different EVP promises fulfilled by an employer, including overall rating, culture and values, work-life balance, senior management, compensation and benefits, and career opportunity based on a five-point (star) scale.…”
Section: Crowdsourced Employer Ratings and Employee Recommendations Omentioning
confidence: 99%
“…To better understand an employer brand, conducting text mining from crowdsourced data on social media, such as Glassdoor, would be a good way, beyond quantitative ratings [3], which is called employer brand intelligence [13]. Even having higher employer ratings on Glassdoor, conducting text mining from posted comments (pros and cons) can identify important insights regarding whether employees are satisfied or dissatisfied.…”
Section: Us Fortune 500 Ranking and Crowdsourced Employer Ratings Omentioning
confidence: 99%
See 2 more Smart Citations
“…Kucherov and Zavyalova (2012) conclude, based on the research results, on significant differences in economic indicators, HRD practices and talent management in companies with a built-in employer brand and companies that do not have this type of asset developed. Kashive, Khanna and Bharthi (2020) conclude that social value is important for the employer brand value assumptions and interest value and work-life value. Maurya and Agarwal (2018) found that organizational talent management is strongly and positively related to the perception of employer branding.…”
Section: Employer Brandmentioning
confidence: 90%